The Effectiveness of Project-Based Learning-Based LKPD Lapbook on Science Literacy in Grade V Elementary School - Enung Nurhasanah; Mintarsih Arbarini (Al-Madrasah: Jurnal Ilmiah Pendidikan Madrasah Ibtidaiyah, 2026)
Education in the 21st century requires students to develop broad scientific understanding and strong thinking skills. However, elementary school students still demonstrate limited scientific knowledge, particularly in topics related to the human digestive system. This study investigates the effect of Project-Based Learning (PjBL) integrated with student worksheets and lapbook (LKPD-Lapbook) media on improving the scientific literacy of fifth-grade elementary students. The research employs a quantitative approach with a quasi-experimental pretest–posttest control group design. The participants consisted of 42 students divided into two groups: an experimental class and a control class, each comprising 21 students. The research instruments included a scientific literacy test, a learning implementation observation sheet, and a student questionnaire. Data analysis was conducted using prerequisite tests of normality and homogeneity, followed by hypothesis testing through an independent samples t-test. In alignment with the Merdeka Curriculum, this study is expected to contribute to the development of innovative IPAS (Integrated Science and Social Studies) learning approaches and provide an alternative contextual learning media to support scientific literacy improvement in elementary schools.